Inter-examiner variability and agreement of the alternate prism cover test (APCT) measurements of strabismus performed by 4 examiners*. (December 2014) - de Jongh, E.; Leach, C.; Tjon-Fo-Sang, M.J.; Bjerre, A.
Abstract Purpose: To investigate the inter-examiner variability and agreement of the alternate prism cover test (APCT) measurements of strabismus at near and distance fixation performed by 4 examiners. Methods: Forty-one participants (median age 12 years, range 3–74) with horizontal strabismus completed APCT measurements at near (1/3 m) and distance (5 m) fixation. Each participant was assessed by 4 masked experienced orthoptists on the same visit. Bland-Altman plots and inter-examiner variability (1.96xSD of the difference) were used to determine a clinical value suggestive of real change. Results: The inter-examiner variability was ±10 prism diopters (PD) at near and ±9 PD at distance fixation. The mean difference between measurements per examiner pair for near fixation ranged between −3 and 1.5 PD, with inter-examiner variability ranging between ±6.9 and ±12.5 PD, and mean difference for distance fixation between −0.8 and 1.6 PD, with inter-examiner variability ranging between ±7.5 and ±11.7 PD. Larger variability was found between some examiner pairs than others. Magnitude of the deviation, test distance, and age had no significant influence on the variation in APCT measurement. Conclusion: A variation in APCT measurement between 4 examiners of less than 10 PD for both near and distance fixation is likely to be due to inter-examiner variability. Changes of 10 PD or more are suggestive of a real change and may be employed as a management threshold.